2021
DOI: 10.3390/ijms222112082
|View full text |Cite
|
Sign up to set email alerts
|

Memory Disorders Related to Hippocampal Function: The Interest of 5-HT4Rs Targeting

Abstract: The hippocampus has long been considered as a key structure for memory processes. Multilevel alterations of hippocampal function have been identified as a common denominator of memory impairments in a number of psychiatric and neurodegenerative diseases. For many years, the glutamatergic and cholinergic systems have been the main targets of therapeutic treatments against these symptoms. However, the high rate of drug development failures has left memory impairments on the sideline of current therapeutic strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 150 publications
0
6
0
Order By: Relevance
“…This study also observed learning and memory impairment in rats after LPC injection, consistent with previous findings. Administration of LPC causes neuronal loss in various parts of the hippocampus and results in cognitive impairment (29). Injecting LPC into the CA1 region of the hippocampus triggers microglia to produce pro-inflammatory cytokines (30).…”
Section: Discussionmentioning
confidence: 99%
“…This study also observed learning and memory impairment in rats after LPC injection, consistent with previous findings. Administration of LPC causes neuronal loss in various parts of the hippocampus and results in cognitive impairment (29). Injecting LPC into the CA1 region of the hippocampus triggers microglia to produce pro-inflammatory cytokines (30).…”
Section: Discussionmentioning
confidence: 99%
“…There was a report that 5-HT4R decreases in the hippocampus and cortex of AD patients [ 36 ]. Moreover, 5-HT4R agonists therapy was reported to increase BDNF, a neurogenesis marker, and to enhance synaptic plasticity, making it a potential therapeutic strategy for ameliorating memory, mood, and feeding behavior disturbances [ 16 , 37 ]. The administration of 5-HT7R agonists also reportedly contributed to improved memory formation [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported a significant loss of 5-HT 4 receptors (5-HT4R) in hippocampal and cortical neurons in AD patients [ 15 ]. The activation of 5-HT4R was shown to benefit cognition in rodents and primates [ 16 ]. A preclinical study suggested that 5-HT7R agonists might be useful in treating memory impairments associated with aging or AD [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…And that hippocampal-related behavioral task was improved with both 5-HT4R agonists. 5-HT4R/AC/PKA/CREB genes are decreased with exacerbated tau aggregation in human post-mortem brains 5-HT4R plays an essential role in processes related to learning and memory mediated by the dominant synapse to nucleus signaling cascade through AC/cAMP/PKA pathway, modulating the expression of plasticity/learning-related proteins such as BDNF, AKT, and CREB (Roux et al, 2021). To assess the mRNA expression levels of the canonical proteins in this cascade (5-HT4, Gsα, Gβ, Gγ, AC, PKA R, and C subunits and CREB), we performed bioinformatics analyses from bulk and single nucleus RNA sequencing from available datasets.…”
Section: -Ht4r Stimulation Reduced Synaptic Taumentioning
confidence: 99%